Pengaruh Pre-Operative Teaching Islami Terhadap Tingkat Cemas Pasien Pre-Operasi TUR-P di RSI Jemursari Surabaya - Sari, Ratna Yunita; Rohmawati, Riska; Faizah, Imamatul; Heris, Wesiana (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Transurethral Resection of the Prostate (TURP) is a surgical procedure to treat benign prostate hyperplasia. The planned surgical procedure will make the patient feel anxious. The purpose of this study was to determine the effect of Islamic-based preoperative teaching on the anxiety level of TUR-P preoperative patients in the Azzara 2 hospital room. Islam Jemursari Surabaya. Quasi-experimental research design with a pre and post-test control group design approach. The sample size used 24 residential respondents, which were then divided into 12 respondents in the intervention group and 12 respondents in the control group. The procedure is performed when the patient is hospitalized until near the operation. Data collection was carried out by measuring the level of anxiety before and after the Islamic-based preoperative teaching. Data were then analyzed using the Willcoxon and Mann Whitney tests. The results showed that Islamic-based preoperative teaching affected reducing anxiety levels in pre-operative patients. TUR-P analysis of the Mann-Whitney test showed a p-value of 0.002. The conclusions of the study show that Islamic-based preoperative teaching can reduce patient anxiety levels, nurses should be able to apply Islamic-based preoperative teaching to overcome anxiety experienced by patients before surgery.Keywords: TUR-P, Islami Preoperative Teaching, Anxiety